PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PT SRI REJEKI ISMAN TBK - Marita Adityawati (Universitas Slamet Riyadi, 2015)
This study aims to analyze a significant the effect of the current ratio on the growth of the profit; a significant the effect of the total debt to total assets ratio on the growth of the profit; a significant the effect of the return on assets ratio on the growth of the profit; a significant the effects of the current ratio, total debt to total assets ratio, and return on assets ratio as an simultaneous on the growth of the profit. It was secondary study use annual finance report documentation. They were analyzed using the multiple regression technique. There is a no significant effect of the current ratio on the growth of the profit; there is a significant effect of the total debt to total assets ratio on the growth of the profit; there is a significant effect of the return on assets ratio on the growth of the profit. The current ratio, total debt to total assets ratio, return on assets ratio variables give a contribution of 97,7 percent. Keywords: growth of the profit, current ratio, total debt to total assets ratio, return on assets ratio